The Podcasting Phenomenon: Genre Synthesis, the Role of Interviews, and Application Possibilities in the Media Context (Herald of Journalism, 2026)
The modern development of genres in digital media, their transformation, and the emergence of new formats require ongoing research. In this regard, the goal of our study is to systematically analyze the genre evolution of podcasts, the peculiarities of the interview format, and the prospects for their development. The study covers the following main areas: a historical overview of the podcast genre, a classification of genres, and the interrelation of the interview format with podcasts.The scientific significance lies in contributing to the theory of new media through the analysis of the transformation of the interview genre in podcasting; the practical significance lies in providing suggestions for the further development of podcast content in the mass media of Kazakhstan.The methodological foundation of the research includes literature analysis, statistical data, the study of popular interview podcasts, and an overview of media practices in Kazakhstan.The result to be identified is that podcasting, which began in 2004 with shows managed by iPods, has evolved into a global market with an emphasis on the interview format. Interviews as a format have been integrated through platforms like YouTube and others. In Kazakhstan, despite audience interest, the necessary infrastructure and technological base have not yet been fully developed. The research findings reveal the interactive role of the interview genre in journalism and the potential for audience engagement.From this perspective, the study contributes to the theory of Kazakhstani and new media. The practical significance includes proposals for mass media to attract a youth audience through podcasts, diversify content, and expand the genre potential of media platforms.
Keywords: podcasting, Kazpodcasting, digital media, media communications, genre transformation, interview podcast, media industry of Kazakhstan.